Principlist approach to multiple heart valve replacements for patients with intravenous drug use-induced endocarditis - Daly, Daniel (Journal of medical ethics, 2022)
Medical professionals often deny patients who inject opioids a second or third heart valve replacement, even if such a surgery is medically indicated. However, such a position is not well defended. As this paper demonstrates, the ethical literature on the topic too often fails to develop and apply an ethical lens to analyse the issue of multiple valve replacements. This paper addresses this lacuna by analysing the case of Mr Walsh, a composite case which protects the identity of any one patient, through the principlist approach of Beauchamp and Childress. It argues that the hospital should offer Mr Walsh, a second valve replacement because the procedure is: medically indicated, autonomously requested, non-maleficent, beneficent and does not violate a formal account of justice. The paper concludes with clinical ethical guidelines for valve surgery for patients with opioid use disorder.